Perfectly conducting graphene electronic waveguide with curved channels. (17th July 2018) - Mosallanejad, Vahid; Wang, Ke; Qiao, Zhenhua; Guo, Guoping
Abstract: We theoretically investigate the electronic transport properties of curved graphene waveguides by employing non-equilibrium Green's function techniques. We systematically study the dependence of the confined waveguide modes on the potential difference, the width of waveguide and side barrier. Through two-terminal electronic transport calculations, we show that the conductance of confined waveguide modes is rather robust against the bending degree of waveguide, in consistence with the band insensitivity to the side barrier. This finding of the perfectly conducting channels strongly suggests the possibility of applying the graphene waveguide in the design of low-power nanoelectronics.